Pendekatan Data Science terhadap Pemilu 2024: Memahami Persepsi Publik dan Tren Opini Politik - Madika, Fiwi Fishinsky; Mailoa, Evangs (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
In this study, Twitter is used as a data source to analyze sentiment and public opinion related to the 2024 General Election. The sentiment analysis method is employed to understand how public views are reflected in tweets containing relevant hashtags. The research aims to identify trends in political opinion and public perception that emerge on Twitter during a specific period before, during, and after the election. By analyzing relevant tweet data, this study will provide in-depth understanding of how public opinion evolves and changes over time, as well as identifying the most influential and popular accounts in political discussions on Twitter. The results show that the majority of public opinion about the 2024 General Election on Twitter is positive, with dominant support and sympathy for presidential candidates. Social network analysis reveals a well-structured network with @eternaciumentaa being the most influential and @geloraco being the most popular